Three zinc iodide complexes based on phosphane ligands: syntheses, structures, optical properties and TD–DFT calculations. Issue 3 (23rd February 2018) - Chen, Di; Wang, Qiu-Hua; Chai, Wen-Xiang; Song, Li
Abstract : ZnI2 (PPh3 )2 and ZnI2 [( p ‐Tol)3 P]2 ( p ‐Tol is p ‐toluene) are both mononuclear four‐coordinated ZnI2 complexes, while [Zn(dppmO2 )3 ][ZnI4 ] [dppmO2 is bis(diphenylphosphoryl)methane] is composed of a [Zn(dppmO2 )3 ] 2+ cation and a [ZnI4 ] 2− anion. The acentric space group of ZnI2 [( p ‐Tol)3 P]2 suggests it as a potential second‐order NLO material. A TD–DFT study demonstrates that the photoluminescence should be derived from the emissive XLCT excited state. Abstract : Three zinc iodide complexes based on phosphane ligands, namely diiodidobis(triphenylphosphane‐κ P )zinc(II), [ZnI2 (C18 H15 P2 )2 ], (1 ), diiodidobis[tris(4‐methylphenyl)phosphane‐κ P ]zinc(II), [ZnI2 (C21 H21 P2 )2 ], (2 ), and [bis(diphenylphosphoryl)methane‐κ 2 O, O ′]zinc(II) tetraiodidozinc(II), [Zn(C25 H22 O2 P2 )3 ][ZnI4 ], (3 ), have been synthesized and characterized. Single‐crystal X‐ray diffraction revealed that the structures of (1 ) and (2 ) are both mononuclear four‐coordinated ZnI2 complexes containing two monodentate phosphane ligands, respectively. Surprisingly, (2 ) spontaneously forms an acentric structure, suggesting it might be a potential second‐order NLO material. The crystal structure of complex (3 ) is composed of two parts, namely a [Zn(dppmO2 )3 ] 2+ cation [dppmO2 is bis(diphenylphosphoryl)methane] and a [ZnI4 ] 2− anion. The UV–Vis absorption spectra, thermal stabilities and photoluminescence spectra of the title complexes have also been studied. Time‐dependent density functional theory (TD–DFT) calculations reveal that the low‐energy UV absorption and the corresponding light emission both result from halide‐ligand charge‐transfer (XLCT) excited states.